A rare localization of Ewing's Sarcoma in the coracoid process: A case report and literature review on scapular Ewing's sarcomas - N. Bahlouli; F. Chait; C. Faraj; S. Choumad; I. Lahlou; N. Allali; M. Maachi; N. Lamalmi; L. Chat; S. El Haddad (Radiology Case Reports)
Ewing's sarcoma can affect any bone. Primary localization in the coracoid process is extremely rare and atypical. In the literature there have been a few reports of Ewing's sarcoma of the scapula. We report the case of an adolescent who presented to our department for investigation of a swelling in the left shoulder. Imaging revealed an osteolytic mass centered on the coracoid process. Histological study was in favor of Ewing's sarcoma.